Gaining insight into irrational off‐label use of vidarabine through analysis of a spontaneous reporting system in China. (2nd July 2020) - Li, Haona; Deng, Jianxiong; Yu, Peiming; Deng, Lewen; Ren, Xuequn
Abstract: What is known and objective: Although superseded by other antiviral agents in many Western countries, vidarabine is still widely used in some countries, including China; hence, the extent and appropriateness of vidarabine prescriptions in children require better characterization. This study examined the rationale, extent, and health risks associated with irrational off‐label vidarabine use in China. Methods: Data used in the study were extracted from a multi‐provincial joint adverse drug reactions monitoring platform from 2002 to 2018. Descriptive statistics were used to analyse the characteristics of individual case safety reports (ICSRs) related to vidarabine use. Results and discussion: Among 2772 individual ICSRs related to vidarabine, 2223 (80.19%) cases occurred in patients aged 0‐9. In all patients, the median age and interquartile range were 2 (0‐6). Although most adverse events were mild, five deaths were recorded, all in children below 7 years of age. Paediatric use is the most prominent off‐label use of vidarabine. Additionally, several other irrational off‐label uses were identified, including 218 (7.86%) cases of overdosing and numerous applications beyond the approved indications, dosages, routes of administration, and solvents. What is new and conclusion: Data indicate that vidarabine was mainly prescribed for suspected common viral infections in paediatric patients, demonstrating serious inappropriate off‐label uses. The problem was further complicated by the lack of sufficient information regarding safety, efficacy, and dosing regimens in children, as well as by several additional risk factors such as inappropriate solvents, routes of administration, and overdose. In the case of children, the physicians' lack of understanding of antiviral activities and compassionate prescriptions were mainly responsible for drug overuse. The health risks associated with the paediatric use of vidarabine in China require greater attention and further investigation. Abstract : Gaining insight into irrational off‐label use of vidarabine through analysis of Individual Case Safety Reports (ICSRs) from a multi‐provincial joint adverse drug reactions monitoring platform in China.